Out of Sync Subnational Housing Markets and Macroprudential Policies - Michael Funke; Petar Mihaylovski; Adrian Wende (Center for Economic Studies and ifo Institute (CESifo), 2018)
In view of regional house prices drifting apart, we examine whether regionally differentiated macroprudential policies can address financial stability concerns and moderate house price differences. To this end, we disaggregate both the household sector and the housing stock in a two-region DSGE model with out of sync subnational housing markets and compare four macroprudentail policy types: standard monetary policy by means of a standard Taylor rule, leaning against the wind monetary policy, national macroprudential policy or one that targets region-specific LTV ratios. In terms of reducing variances of house prices, regionally differentiated macroprudential policy performs best, provided the policy authorities are concerned with stabilising output and house prices rather than simply minimising the variance of inflation. Thus the findings point to a critical role for policy in regionalising macroprudential tools.
Keywords: E32; E44; E52; E58; 330; macroprudential policies; housing; DSGE; Great Britain